2015
DOI: 10.1111/jre.12334
|View full text |Cite
|
Sign up to set email alerts
|

Ankaferd blood stopper enhances healing after osseous grafting in patients with intrabony periodontal defects

Abstract: The findings suggest that ABS enhances the soft tissue healing during the periodontal defect fill by the ACB by stimulating angiogenesis and vascular endothelial cell function, prevents GR and thereby increases the clinical attachment gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…One possible factor which could explain this result can be attributed to that, ABS hasn't affected on soft tissue parameters This result are consistent with Pamuk, et al in 2016. who explained the clinical efficacy of (ABS) when used in combination with autogenous cortical bone graft (ACB) in the treatment of intrabony periodontal defects. The authors stated that no significant differences in PI, GI, PPD observed between the groups (16) . GÜL, et al explained effect of ABS on bone healing.…”
Section: Discussionmentioning
confidence: 94%
“…One possible factor which could explain this result can be attributed to that, ABS hasn't affected on soft tissue parameters This result are consistent with Pamuk, et al in 2016. who explained the clinical efficacy of (ABS) when used in combination with autogenous cortical bone graft (ACB) in the treatment of intrabony periodontal defects. The authors stated that no significant differences in PI, GI, PPD observed between the groups (16) . GÜL, et al explained effect of ABS on bone healing.…”
Section: Discussionmentioning
confidence: 94%
“…Pellati et al (2009) and Motsei et al (2003) also demonstrated that 18-beta glycyrrhetinic acid, the key components of ABS, is known to possess a strong antifungal effect on the Candida albicans [36,37]. This property can be utilized for preparing various antifungal mouthwashes for the treatment of oral candidiasis and other fungal infections [47][48][49][50][51][52]. Therefore ABS should be tried as an antiplaque and anti-gingivitis agent for the treatment of gingivitis, periodontitis, periapical, periodontal abscess and postoperative infections following periodontal surgery.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…Pamuk et al (2016) compared the clinical efficacy and expression of Vascular Endothelial-derived Growth Factor (VEGF) upon the use of ABS in combination with autogenous cortical bone graft for the treatment periodontitis induced intra-osseous defects [51]. There was a significant increase in the VEGF concentration when ABS was used along with bone graft as compared to bone graft alone.…”
Section: Regenerative and Anti-apoptotic Propertiesmentioning
confidence: 99%
“…It has been used for centuries in Turkish traditional medicine as a hemostatic agent [4]. ABS has been approved by the Turkish Ministry of Health as a topical hemostatic agent for the management of dermal, external, internal, postoperative, and dental bleeding [14,26,31]. It has been manufactured in buffer, ampoule and spray forms since 2007 [5].…”
Section: Introductionmentioning
confidence: 99%